Arterial Spin-Labeling and MR Spectroscopy in the Differentiation of Gliomas - Chawla, S.; Wang, S.; Wolf, R.L.; Woo, J.H.; Wang, J.; O'Rourke, D.M.; Judy, K.D.; Grady, M.S.; Melhem, E.R.; Poptani, H. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Noninvasive grading of gliomas remains a challenge despite its important role in the prognosis and management of patients with intracranial neoplasms. In this study, we evaluated the ability of cerebral blood flow (CBF)-guided voxel-by-voxel analysis of multivoxel proton MR spectroscopic imaging (1H-MRSI) to differentiate low-grade from high-grade gliomas.MATERIALS AND METHODS: A total of 35 patients with primary gliomas (22 high grade and 13 low grade) underwent continuous arterial spin-labeling perfusion-weighted imaging (PWI) and 1H-MRSI. Different regions of the gliomas were categorized as “hypoperfused,” “isoperfused,” and “hyperperfused” on the basis of the average CBF obtained from contralateral healthy white matter. 1H-MRSI indices were computed from these regions and compared between low- and high-grade gliomas. Using a similar approach, we applied a subgroup analysis to differentiate low- from high-grade oligodendrogliomas because they show different physiologic and genetic characteristics.RESULTS: Choglioma (G)/white matter (WM), GlxG/WM, and Lip+LacG/CrWM were significantly higher in the “hyperperfused” regions of high-grade gliomas compared with low-grade gliomas. ChoG/WM and Lip+LacG/CrWM were also significantly higher in the “hyperperfused” regions of high-grade oligodendrogliomas. However, metabolite ratios from the “hypoperfused” or “isoperfused” regions did not exhibit any significant differences between high-grade and low-grade gliomas.CONCLUSION: The results suggest that 1H-MRSI indices from the “hyperperfused” regions of gliomas, on the basis of PWI, may be helpful in distinguishing high-grade from low-grade gliomas including oligodendrogliomas.